Supplementation of multienzyme with acidifier alleviates the antinutritional effects of a high soybean meal diet for nursery pigs - Ashir F. Atoo; Andres F. Bolivar-Sierra; Jorge Y. Perez-Palencia; Crystal L. Levesque; Rob Patterson; Hari B. Krishnan; Jinsu Hong; Jinsu Hong (Frontiers in Veterinary Science)
IntroductionThe current study aimed to alleviate these negative impacts in diets containing high levels of SBM by supplementation of an enzyme combination solely or together with an acidifier.MethodsA total of 240 weaned pigs (average body weight of 5.9 kg), were allotted to 5 dietary treatments with 8 replicates in a randomized complete block design. Dietary treatments were low soybean meal (SBM) diet (17 and 20% in phase 1 and 2), medium SBM diet (22 and 25% in phase 1 and 2), high SBM diet (30% in and 35% in phase 1 and 2), high SBM diet with multienzyme supplementation, and high SBM diet with multienzyme and acidifier supplementation. All pigs were fed a common corn-SBM-based diet in phase 3. Growth performance was measured at the end of each phase along with blood collection. One pig per pen was euthanized to collect intestinal tissue for histomorphology and ileal digesta for the analysis of secretory IgA (sIgA).ResultsPigs fed high SBM diets with multienzyme or with multienzyme and acidifier tended to have a greater (p < 0.10) ADG compared to pigs fed High-SBM diet during phase 2 by 12.5%. During the 2nd week, pigs fed high SBM diets supplemented with multienzyme or multienzyme plus acidifier had less (χ2 < 0.05) diarrhea incidence than those fed high SBM diet. Dietary treatment did not affect the serum concentration of T4, IGF-1, IgA, and IgE. Pigs fed high SBM diet with multienzyme and acidifier supplementation had a lower (p < 0.05) concentration of sIgA in the ileal digesta on d 14 compared to high SBM diet, which was similar to low SBM diet. Except for Gly and Pro, pigs fed high SBM diets with enzyme and acidifier had improved apparent ileal digestibility of amino acids, which were higher (p < 0.05) than those fed high SBM and similar to those fed low SBM diets.ConclusionSupplementation with multienzyme or multienzyme and acidifier in high SBM diets could reduce the negative impact of high SBM inclusion in nursery pig diets by improving amino acids digestibility and reducing allergenic response in nursery pigs.